A European perspective on dental cone beam computed tomography systems with a focus on optimisation utilising diagnostic reference levels - Siiskonen, Teemu; Gallagher, Aoife; Ciraj Bjelac, Olivera; Novak, Leos; Sans Merce, Marta; Farah, Jad; Dabin, Jérémie; Malchair, Françoise; Knežević, Željka; Kortesniemi, Mika (Journal of radiological protection, 2021)
Cone beam computed tomography (CBCT) has been available since the late 1990s for use in dentistry. European legislation requires optimisation of protection and the use of diagnostic reference levels (DRLs) as well as regular quality control (QC) of the imaging devices, which is well outlined in existing international recommendations. Nevertheless, the level of application is not known. Earlier studies have indicated that few European countries have established DRLs and that patient doses (exposure parameters) have not been properly optimised. The EURADOS Working Group 12-Dosimetry in Medical Imaging undertook a survey to identify existing practices in Member States. Questionnaires were developed to identify equipment types, clinical procedures performed, and exposure settings used. The surveys were circulated to 22 countries resulting in 28 responses from 13 countries. Variations were identified in the exposure factors and in the doses delivered to patients for similar clinical indicators. Results confirm that patient doses are still not properly optimised and DRLs are largely not established. There is a need to promote the importance of performing QC testing of dental CBCT equipment and to further optimise patient exposure by establishment and use of DRLs as a part of a continuous optimisation process.
Keywords: Humans; řízení kvality; Radiometry; dávka záření; počítačová tomografie s kuželovým svazkem; radiometrie; Cone-Beam Computed Tomography; Diagnostic Reference Levels; diagnostické referenční úrovně; Quality Control; lidé; Radiation Dosage